2020
DOI: 10.1017/hpl.2020.14
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic electron acceleration by surface plasma waves excited with high intensity laser pulses

Abstract: The process of high energy electron acceleration along the surface of grating targets (GTs) that were irradiated by a relativistic, high-contrast laser pulse at an intensity $I=2.5\times 10^{20}~\text{W}/\text{cm}^{2}$ was studied. Our experimental results demonstrate that for a GT with a periodicity twice the laser wavelength, the surface electron flux is more intense for a laser incidence angle that is larger compared to the resonance angle predicted by the linear model. An electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
1
14
0
1
Order By: Relevance
“…Thus, the pulse contrast is improved up to 10 -12 in hundreds of picoseconds and to 10 -9 in a few picoseconds before the pulse peaks. Previous experimental and numerical studies confirm a preplasma expansion in the range of tens of nm before the main interaction [27,28,33,34] . Further physical parameters of the laser system are described by Cerchez et al [56] , allowing an insight into the different experimental configurations.…”
Section: Test Experiments Demonstrating the Usability Of The Micro-gratings For Laser-plasma Applicationsmentioning
confidence: 62%
See 1 more Smart Citation
“…Thus, the pulse contrast is improved up to 10 -12 in hundreds of picoseconds and to 10 -9 in a few picoseconds before the pulse peaks. Previous experimental and numerical studies confirm a preplasma expansion in the range of tens of nm before the main interaction [27,28,33,34] . Further physical parameters of the laser system are described by Cerchez et al [56] , allowing an insight into the different experimental configurations.…”
Section: Test Experiments Demonstrating the Usability Of The Micro-gratings For Laser-plasma Applicationsmentioning
confidence: 62%
“…These kinds of observations are possible due to the µm transverse dimension of the target, which allows investigations over (almost) the full angular range around the interaction point. One may note that these effects can be obscured by the intrinsic temporal profile of high-intensity laser pulses [27,[31][32][33][34][35] . A target will always be irradiated prior to the main peak by the relatively lowintensity, nanosecond background (amplified spontaneous emission) and pre-pulses and, thus, a preplasma will be created with a spatial expansion of the order of micrometres.…”
Section: Introductionmentioning
confidence: 99%
“…The high intensity and ultra-short laser-plasma interaction regime (≤ 10 19 W/cm 2 and ≤ 100f s), showed that a significant percentage of electrons trapped in the SPW can be accelerated along the surface in the range of ∼ 10 MeV [15][16][17][18][19][20]. High charge electron bunches (up to ∼ 650 pC) were also observed [20][21][22][23][24] with applications including the generation of bright sources of ultra-short pulsed X-rays, ultra-fast electron diffraction, tabletop electron accelerators, and ultra-fast electron spectroscopy [25][26][27][28]. Recently, a scheme exploiting up to date laser techniques was proposed for controlling the duration and amplitude of SPWs by which a laser with an intensity of a few 10 19 W/cm 2 and a pulse duration of a few tens of f s should be able to accelerate electrons up to ∼ 70MeV [21].…”
Section: Introductionmentioning
confidence: 96%
“…We employed 2D Particle-In-Cell (PIC) simulations for laser intensities ranging from 10 16 to 10 22 W/cm 2 , for various angles of incidence. The influence of both the plasma density and the grating depth of the modulated plasma surface were investigated since previous studies identified them as important parameters in SPW excitation [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…SPW then become of interest not only as unexplored nonlinear plasma modes but also for their capability of accelerating electrons, being waves with a longitudinal electric field component and slightly subluminal phase speed. Simulations and experiments have indeed shown that relativistic SPW can accelerate high charge, ultrashort electron bunches along the target surface [14][15][16][17][18][19][20][21][22][23][24][25], with energies largely exceeding their quiver energy and spatiotemporal correlation with extreme ultraviolet (XUV) harmonic emission [26].…”
mentioning
confidence: 99%